THU0236 The TNF Alpha -308 and the IL-6 -174 Promoter Polymorphisms Associate with Effective Anti-TNF Alpha Treatment in Seronegative Spondyloarthritis. (9th June 2015) - Fabris, M.; Quartuccio, L.; Fabro, C.; Sacco, S.; Lombardi, S.; Ramonda, R.; Biasi, D.; Punzi, L.; Adami, S.; Olivieri, I.; Curcio, F.; De Vita, S.
Abstract : Background: One of the most important outcomes of treatment in SpA is the retention rate of therapy in the long term. Many genetic studies in chronic polyarthritis reported a correlation between response to anti-TNF therapy and several single nucleotide polymorphisms (SNPs), but the usefulness of this finding when related to the clinical outcome is ill defined. Objectives: The primary endpoint of this study was to establish a possible correlation between several genetic polymorphisms, including ones never investigated before in SpA, and the retention rate of the first TNFa blocking agent, by comparing patients needing to switch the first anti-TNFa agent (Sw) to patients not needing to switch (NSw). To distinguish these two groups, a follow-up of at least one year was required. Methods: 187 consecutive SpA patients (124 males and 63 females; mean age 52±30 years) were studied. All the patients had been followed up for at least 12 months after the introduction of the first anti-TNFα agent. The mean disease duration was 30±28 years (range 2-58 years). Seventy-four (39.6%) patients were diagnosed as affected by psoriatic arthritis (PsA), 66 (35.3%) by ankylosing spondylitis (AS) and 47 (25.1%) by undifferentiated spondyloarthritis (uSpA). Six SNPs were analysed: TNFα -308A>G (rs1800629), TNFR2 196M>R, IL-6 -174G>C (rs1800795), IL-6Ra, FCGR3A 158V>F (rs396991) and TGF-beta 869T>C (rs 19822073). The chi-squared or Fisher's exact test and Mann–Whitney's U-test were used. Results: The TNFα and the IL-6 promoter polymorphisms were significantly associated with the NSw phenotype in SpA. In particular, the TNFα -308 AA/AG genotypes were found in 24.4% NSw vs 10.9% Sw patients (p=0.03) and the GG homozygosis of the IL-6 promoter polymorphism in 49.6% NSw vs 34.4% Sw patients (p=0.047). By multivariate analysis, the TNFα -308A allele as well as the presence of the IL-6 -174GG homozygosis resulted as independent biomarkers predicting survival of the first anti-TNFα therapy in SpA (p=0.007, OR 4.4, 95%CI 1.5-13.1, and p=0.035, OR 2.1, 95%CI 1.1-4.4, respectively). Also the male gender (p=0.001, OR 3.4, 95%CI 1.6-7.1) resulted an independent variable associated with the NSw phenotype. The other SNPs, located in the genes encoding TNFR2, IL-6Ra, TGFb and FCGR3A, did not show any significant association. No association was found between the BASDAI or DAS28 response at month +6 (for axial or peripheral involvement, respectively) and all the investigated polymorphisms. The exposure time to the anti-TNFα therapies was significantly higher in NSw in comparison with Sw (NSw: 58±25.9 months vs Sw: 30.8±20.2 months, p<0.0001); thus, the NSw group was not biased by a shorter follow-up under anti-TNFα therapy. Conclusions: The TNFα -308 and the IL-6 -174 promoter polymorphisms appear significantly associated with a higher efficacy of anti-TNFa therapy in SpA, expressed by the retention rate of the first anti-TNFα agent. This confirms the importance of the genetic background to optimize the management of the biologic agents in SpA. Disclosure of Interest: None declared